Improved rice varieties adoption and welfare implications among small-holder farmers in south-west Nigeria: An empirical analysis and prospects for food security - John, Aladejebi Oluwafemi; Ajayi, Omolehin Raphael; Bamidele, Fakayode Segun; Oladipupo, Abiola Matthew; Olushola, Oyewole Samuel (Asian Journal of Agriculture and Rural Development, 2023)
This study examines improved rice variety adoption and its welfare implications among small-holder farmers in South West Nigeria. A multistage sampling technique was used to select 300 rice-farming households from two selected states. The study used primary data retrieved with the aid of structured questionnaires. Data were analysed using a five-point Likert scale, a logistic regression model, and the multidimensional poverty index (MPI). The study showed that more than half (56%) of the farmers noted that the acceptance of improved varieties was easy, with a mean score of 3.5. The study also established that age (β = -0.0394; p < 0.001), farming experience (β = 0.0758; p < 0.001), and extension contact (β = 1.7203; p < 0.001) were the factors that influenced the adoption of improved rice varieties in the study area. The results of the MPI revealed that indigenous rice farmers were poorer than improved rice-farming households. Overall, 34% of improved and 54% of indigenous rice farming households are multidimensionally poor. MPIs of 0.11 and 0.21 were obtained for improved and indigenous farmers, respectively. The adoption of improved varieties was influenced by socioeconomic factors, and some households cultivating rice were MPI-poor. The study indicated that the adoption of improved varieties can result in improved productivity and reduce the prevalence of poverty in the study area.